Identifikasi Cekungan Sumatera Tengah Berdasarkan Data Anomali Geomagnetik Reduce to The Pole dan Metode Half-Slope - Dewi, Soraya Tiana; Safira, Ayu; Valentino Manurung, Andro; Rasimeng, Syamsurijal; Rustadi (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2024)
The Central Sumatra Basin is a back arc basin which is one of the largest oil-producing basins in Indonesia. This study aims to analyze the magnetic anomaly in the Central Sumatra Basin using the Reduce to Pole and Half-Slope methods. The methods in this study include filtering magnetic data from Sumatran geological data, making a map of the total magnetic field anomaly, and carrying out a reduction transformation to the poles in the form of a monopole, followed by 3 slices of RTP data slices, then calculating Half-Slope using RTP data slices. using Matlab software. The total magnetic field value before Reduce to Pole (RTP) was in the range of -90 to 60 nT. The value after Reduce to Pole (RTP) is in the range of -140 to 190 nT. In the results of slice 1, the average depth value is 59.2 km. Slice 2 results obtained an average depth value of 35.2 km. The average depth value on slice 3 is 42.8 km. Determine the basin boundary and slice the data in the basin boundary area for analysis using the half-slope method. Obtained an average value of depth at the boundary of the Central Sumatra basin of 19.6 km.